Amylase potential of filamentous fungi isolated from sweet potato pulp - Mello Grizafis, Vanessa Kamila; Alberti Gomes, Jaime; Alvim Veiga Pileggi, Sônia; Masetto Antunes, Sandra Regina; Maidl de Souza, Nátali; Weirich Neto, Pedro Henrique (Revista Brasileira de Engenharia de Biossistemas, 2023)
Sweet potato is a rustic culture, widely adapted and with a high starch content, thus having innumerable aptitudes. For the transformation of sweet potatoes into biofuel, some processes are necessary. The success of ethanol production from sweet potatoes depends on the transformation of starch into fermentable sugars. The most used conversion process is enzymatic hydrolysis, which uses commercially available enzymes. However, this process can be carried out through enzymes secreted by filamentous fungi. In this work, filamentous fungi that naturally colonized sweet potatoes were studied. These were isolated, tested for enzymatic activity, and identified by microculture. Fifty-one fungi from the pulp of sweet potatoes Beauregard and BRS-Amélia were isolated, 27 of them showed the ability to hydrolyze starch. Out of these, six showed an enzyme index ≥ 2.0 and were identified as Aspergillus sp. and Penicillium sp. This fact indicates the potential of these fungi in the production of amylase, an important enzyme for ethanol production.